ANALISIS POTENSI, REALISASI DAN KINERJA ORGANISASI PENGELOLA ZAKAT BAZNAS TULUNGAGUNG. - Aswad, Muhammad; Ardi, Mulia (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2021)
This study aims to measure the potential, realization and performance of BAZNAS Tulungagung. The problem faced by OPZ has not been able to maximize its role as an institution that receives zakat from the community (muzaki), OPZ BAZNAS is demanded to be professional and build trust so that the public trusts and tithes to it. This study measures the nominal potential and the realization of zakat collected by BAZNAS Tulungagung. With descriptive qualitative methods and based on zakat data and analyzed data from BPS, it is found that Tulungagung Regency is an area with a Muslim population (98%) and economic growth of 5%, per capita income of 23 million rupiah, of course it is potential for collecting zakat funds. In this study, it was found that the zakat realization was Rp. 3.719.296.538, - from a potential of Rp. 153.772.822.140, ​​-. This can be analyzed because, (i) muzaki directly pays zakat to mustahik, (ii) muzaki's low trust in zakat management organizations, (iii) the utilization of zakat funds is not optimal, (iv) low understanding of zakat and (v) low quality of human resources (SDM) as amil zakat, the committees who organize zakat. Meanwhile, the distribution performance of BAZNAS Tulungagung is still dominated by charity patterns and partly empowerment in productive businesses.